The effectiveness of project-based education in developing critical thinking and communication skills in students - Ganieva, Dilshoda (The Lingua Spectrum, 2025)
This article explores the effectiveness of project-based education (PBE) in fostering students’ critical thinking and communication skills within higher education. The study emphasizes how authentic, inquiry-based, and collaborative projects encourage learners to analyze problems from multiple perspectives, evaluate evidence, and construct logical arguments. At the same time, PBE strengthens students’ ability to clearly articulate ideas, negotiate with peers, and adapt communication across diverse contexts. The findings reveal that project-based approaches not only improve academic performance but also enhance intrinsic motivation and engagement, making students more responsible and invested in their learning process. By integrating real-world tasks into the curriculum, students gain transferable skills that are highly valued in the twenty-first-century workforce, such as adaptability, creativity, teamwork, and leadership. The article highlights that project-based education contributes to holistic learner development and prepares graduates for the demands of rapidly changing societies. It concludes that systematic integration of PBE into higher education is essential for cultivating versatile and future-oriented professionals.